2012
DOI: 10.5402/2012/251632
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Clinical Trial of Trametes versicolor in Women with Breast Cancer

Abstract: Introduction. Orally administered preparations from the Trametes versicolor (Tv) mushroom have been hypothesized to improve immune response in women with breast cancer after standard chemotherapy and radiotherapy. Methods. A phase I, two-center, dose escalation study was done to determine the maximum tolerated dose of a Tv preparation when taken daily in divided doses for 6 weeks after recent completion of radiotherapy. Eleven participants were recruited and nine women completed the study. Each cohort was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 20 publications
(17 reference statements)
1
45
0
2
Order By: Relevance
“…In another study done by Cheong-Yip et al [36], ethanolwater extract of T. versicolor exhibited significant antiproliferative activity on three human breast cancer cell lines (MDA-MB-231, MCF-7 and T-47D) in a dose-dependent manner in vitro. Carolyn achieved similar findings et al [37] in a clinical trial on women with breast cancer where oral preparations of T. versicolor administered to the subjects showed significant antiproliferative activity.…”
Section: Discussionsupporting
confidence: 60%
“…In another study done by Cheong-Yip et al [36], ethanolwater extract of T. versicolor exhibited significant antiproliferative activity on three human breast cancer cell lines (MDA-MB-231, MCF-7 and T-47D) in a dose-dependent manner in vitro. Carolyn achieved similar findings et al [37] in a clinical trial on women with breast cancer where oral preparations of T. versicolor administered to the subjects showed significant antiproliferative activity.…”
Section: Discussionsupporting
confidence: 60%
“…T. versicolor anticancer activity was investigated in many studies and reported in many reviews (in experimental cancer models and clinical trials) [2,5,[12][13][14][15]. The majority of reviews and studies are related to the activity of the extracts from this fungus [12,16].…”
Section: Discussionmentioning
confidence: 99%
“…Another important question was the method adopted for mushroom preparations processing. The most common forms of mushroom preparations are extracts [2] and powders (suspensions) [5]. However the comparative studies regarding the effectiveness of certain substances (fractions isolated from the fungus) or mushroom powder (complex of biologically active substances) application are not well presented in the literature.…”
Section: Advances In Biomedicine and Pharmacy (An International Journmentioning
confidence: 99%
“…Owing to its effect on the immune system, the YZP protein is able to suppress inflammation, which is a desirable phenomenon in cancer treatment [50]. An extract of T. versicolor was shown to be a safe immunostimulant which can support chemotherapy and improve patient's condition generally [51]. The anti-tumor effect in breast cancer is attributed to the PSP and PSK (Krestin) polysaccharopeptides, which act on the immune system and mediators of inflammation [19].…”
Section: Trametes Versicolormentioning
confidence: 99%